STUDY OF IRGANAI SETTLEMENT I IN THE AREA OF CONSTRUCTION OF IRGANAI HYDROELECTRIC STATION IN MOUNTAINOUS DAGESTAN IN 2006 - Ataev, G D (History, Archeology and Ethnography of the Caucasus, 2017)
The article presents the results of archaeological study of Irganai settlement I of the Middle and early stage of the Late Bronze Age in the area of construction of Irganai hydroelectric station in 2006. A rectangular stone room discovered in 2005 was revealed and partly delineated.In the south-eastern part of the excavation site, a stone wall was identified, it runs westward and is perpendicular to the southern wall of the room discovered and partially excavated in 2004-2005. It has been established that the western end of wall 1is connected to the one revealed in 1986. Stone wall 1 is wideand mainly single-row, its small western part is double-row. The length of stone wall 1 revealed in 2006 is 4.2 m. The total length of the wall including the part excavated in 1986 is 5.8 m, and the height of the preserved wall ranges from 1.6 to 1.8 m. A significant archaeological material was found there: tools, ceramics, as well as considerable osteological material. Research of 2006has revealed a new interesting data for cultural and historic interpretation of the Bronze Age sites of the Irganai basin and the mountainous part of Dagestan. The materials from Irganai settlement I found during excavations of 2006, date back to 18th-14th centuries BC. Study of the materials from Irganai settlement I and Irganai burial I along with the materials from earlier excavations allow to establish Irganai local variant of the Ginchi-Gatynkali culture of early stage of the Bronze Age of Mountainous Dagestan and Southeast Chechnya.